Hirearki Peraturan Perundang-Undangan Indonesia - Muhammad Naufal Hakim (CV. Lenggogeni Data Publishing, 2024)
Regarding the hierarchy of laws and regulations, there are two issues that are often discussed. First, whether or not to include the People's Consultative Assembly (MPR) Decree in the hierarchy of laws and regulations (Article 7 paragraph (1) of Law 12/2011). Second, the relevance of the inclusion of regulations of state institutions, agencies, or commissions such as regulations of the House of Representatives (DPR), the Regional Representatives Council (DPD), and even Regulations of the Supreme Audit Agency (BPK) or Bank Indonesia as statutory regulations (Article 8 paragraph (1) of Law 12/2011). The key questions to discuss both are: what types of regulations can be categorized as laws and regulations, so that they can be arranged in a hierarchy? These types need to be explored from the aspect of post-amendment state institutions of the 1945 Constitution as well as the theory and practice of state administration. The author concludes that the MPR Decree does not need to be included in the types and hierarchy of laws and regulations stipulated in Article 7 paragraph (1) of Law 12/2011. Therefore, there needs to be an amendment to Article 7 paragraph (1) to remove MPR Decrees from the list. On the other hand, the DPR needs to fulfill its unwritten political duty to ensure that all laws mandated by the